The effect of pre- and probiotic supplementation on inflammatory markers in post-menopausal women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Branch, Rebecca (Massey University, 2023)
Background: Chronic inflammation is linked with several deleterious diseases, including cardiovascular disease, diabetes mellitus, irritable bowel disease, and osteoporosis. Post-menopausal women are at a heightened risk of developing these diseases due to the remission of oestrogen, further amplifying a pro inflammatory state. Objectives: This study aimed to critically examine the combined effect of synbiotic supplementation and exercise in the form of ≥7,000 steps per day on inflammatory markers in sedentary post-menopausal women. Method: Eighty-seven healthy post-menopausal women were allocated to receive either a synbiotic supplement or placebo for 12 weeks. Participants' demographics and physical activity levels were determined using questionnaires, and their diet was assessed using self-reported 3-day diet records. Body composition measures of height, weight and BMI were measured at baseline, while total body mass, lean body mass, total fat mass and total body fat percentage at baseline and week 12 using dual-energy X-ray absorptiometry. Fasted venous blood samples were collected to analyse inflammatory status before and after the intervention. Statistical analysis was performed using SPSS version 24. Outcome variables with multiple time points were analysed using repeated measures ANOVA with the model, including time, intervention group and their interaction as fixed effects. Results: The results showed no significant differences between the intervention group's demographics, physical activity levels, and dietary intake. The 12-week study duration had a statistically significant effect on lowering hs-CRP, IL-8, IFN γ, TNF-α and increasing IL-6 and IL-10 in both groups. Additionally, the treatment type and study duration significantly impacted IL-10. However, the observed decrease in IL-1β over time was not significant. No significant interactions between time and group were observed across all inflammatory markers. Over time, there was a significant increase in total lean body mass and a decrease in total body fat percentage in both groups. However, the treatment type did not affect total lean body mass, total fat mass, total body mass and percentage body fat in both groups. Conclusion: The current study showed no notable differences between groups, suggesting synbiotic supplementation is likely ineffective at reducing chronic inflammation in post-menopausal women. Future studies must confirm these findings and investigate the effects of exercise and synbiotic supplementation separately.
Keywords: 321004 Nutritional science